Tgfbr1 regulates lateral plate mesoderm and endoderm reorganization during the trunk to tail transition - Anastasiia Lozovska; Ana Casaca; Ana Novoa; Ying-Yi Kuo; Arnon D Jurberg; Gabriel G Martins; Anna-Katerina Hadjantonakis; Moises Mallo (eLife)
During the trunk to tail transition the mammalian embryo builds the outlets for the intestinal and urogenital tracts, lays down the primordia for the hindlimb and external genitalia, and switches from the epiblast/primitive streak (PS) to the tail bud as the driver of axial extension. Genetic and molecular data indicate that Tgfbr1 is a key regulator of the trunk to tail transition. Tgfbr1 has been shown to control the switch of the neuromesodermal competent cells from the epiblast to the chordoneural hinge to generate the tail bud. We now show that in mouse embryos Tgfbr1 signaling also controls the remodeling of the lateral plate mesoderm (LPM) and of the embryonic endoderm associated with the trunk to tail transition. In the absence of Tgfbr1, the two LPM layers do not converge at the end of the trunk, extending instead as separate layers until the caudal embryonic extremity, and failing to activate markers of primordia for the hindlimb and external genitalia. The vascular remodeling involving the dorsal aorta and the umbilical artery leading to the connection between embryonic and extraembryonic circulation was also affected in the Tgfbr1 mutant embryos. Similar alterations in the LPM and vascular system were also observed in Isl1 null mutants, indicating that this factor acts in the regulatory cascade downstream of Tgfbr1 in LPM-derived tissues. In addition, in the absence of Tgfbr1 the embryonic endoderm fails to expand to form the endodermal cloaca and to extend posteriorly to generate the tail gut. We present evidence suggesting that the remodeling activity of Tgfbr1 in the LPM and endoderm results from the control of the posterior PS fate after its regression during the trunk to tail transition. Our data, together with previously reported observations, place Tgfbr1 at the top of the regulatory processes controlling the trunk to tail transition.